(untitled) (International Journal of Built Environment and Sustainability, 2025)
Student Learning Outcomes (SLOs) play a crucial role in contemporary educational curricula. While a considerable body of research has focused on the development and effectiveness of SLOs, there has been limited exploration of their use for examining other academic phenomena. A school’s teaching philosophy is of critical importance, and course content needs to be designed in alignment with this philosophy. Hypothesizing that the SLOs serve as a concise representation of the course content and a reflection of the school’s underlying philosophy, this study proposes a methodology for evaluating SLOs as part of a broader goal to assess course content, given that SLOs provide measurability. Kolb’s Learning Style Inventory (KLSI) was used as a tool, as it has been cited by scholars for its potential to provide insights into the perspectives of different types of learners. This includes students in various disciplines including architecture, the chosen discipline of this research. A questionnaire, designed by integrating KLSI and SLOs was administered in a case study of architectural design studios. Key findings suggest that the method demonstrates its potential to assess SLOs from the perspective of various types of learners. This includes, but is not limited to, determining whether the SLOs address diverse learner types across various academic levels, whether they prioritize specific learner types at different levels, and whether they maintain a consistent focus on particular learner types throughout all academic years. Additionally, a supporting finding suggests that this approach may provide rational justifications for the SLOs within architectural design studios, highlighting challenges in fully adhering to certain established standards. In this way, this paper introduces a novel application of SLOs in academic contexts and aims to contribute to the alignment of course content with the school’s teaching philosophies, while potentially influencing student intake policies within the field of architecture.